Rescue with intravitreal bevacizumab in aggressive posterior retinopathy of prematurity poorly responsive to laser treatment - Kumar, Vivek; Kinkhabwala, Ravish; Chandra, Parijat; Takkar, Brijesh; Azad, Shorya Vardhan; Azad, Rajvardhan (Annals of Eye Science, 2018)
Successful management of a case of aggressive posterior retinopathy of prematurity (APROP) poorly responsive to laser therapy with intravitreal bevacizumab (IVB) is discussed. IVB is useful as rescue therapy in such cases, if given within the correct window period post laser therapy.